Luxembourg : Financial Sector Assessment Program: Technical Note-Managing Problem Banks and Systemic Banking Crises. (IMF Staff Country Reports; Country Report ;, 2017)
This Technical Note analyzes the bank failure mitigation and resolution regime, as well as arrangements for managing a financial crisis, in Luxembourg. The landscape for managing problem banks in Luxembourg has changed fundamentally in recent years. As part of the euro area, Luxembourg is now part of a banking union in which the European Central Bank (ECB) has exclusive authority to directly supervise significant institutions and the Commission for the Supervision of the Financial Sector (CSSF), under the oversight of the ECB, directly supervises less significant institutions. It is recommended that the CSSF increase staffing for resolution and pay attention to potential conflicts of interest in the decision-making process related to supervisory and deposit insurance functions.